WOMEN IN RAPING CASE REPORT (Analysis of Critical Discourse on Rape Case Reporting on Kompas.com January 2021 - Achirul Satriya Anugrah; Yuli Candrasari (Universitas Islam Balitar, 2021)
In the rape newspublished on Kompas.com daily in January 2021. The victims in reportingthis rape case are women, women are not dominant groups. Women are often the subject of newscoverage by the media, but what is unfortunate about this is that women in the news are often harmedby the media. The purpose of this study is to find out how Kompas.com describes actors in rape newswhich published in January 2021. The research was conducted using the exclusion and inclusionstrategy of Theo Van Leeuwen's critical discourse analysis model to find out the discourse on rapenews based on news texts. The results of the study indicate that there is a text that places the victimin a marginal position by using an identification strategy. However, Kompas.com tends to be neutralin reporting rape cases, conveying to the audience what happened as it is, as well as in conveyingthe two actors as they are